Regularization of One Conditionally Ill-Posed Problem of Extractive Metallurgy - Bolshakov, V.I.; Volchuk, V.M.; Dubrov, Yu.I. (Металлофизика и новейшие технологии, 2018)
One of the ways to solve the conditionally ill-posed problem for ranking quality criteria of the multiobjective system, whose regularization is made by applying the fractal formalism, is hereby considered. Ranking quality criteria by their importance is based on the definition of the area of self-similarity for partial criteria. Рассматривается один из путей решения условно некорректной задачи ранжирования критериев качества многокритериальной системы, регуляризация которой производится применением фрактального формализма. Ранжирование критериев качества по их значимости базируется на определении области самоподобия частных критериев. Розглядається один із шляхів вирішення умовно некоректної задачі ранжування критеріїв якости багатокритеріяльної системи, реґуляризація якої проводиться застосуванням фрактального формалізму. Ранжування критеріїв якости за значенням базується на визначенні области самоподібности окремих критеріїв.